Learning through experimenting: an original way of teaching geometrical optics. (3rd October 2016) - Even, C; Balland, C; Guillet, V
Abstract: Over the past 10 years, we have developed at University Paris-Sud a first year course on geometrical optics centered on experimentation. In contrast with the traditional top-down learning structure usually applied at university, in which practical sessions are often a mere verification of the laws taught during preceding lectures, this course promotes 'active learning' and focuses on experiments made by the students. Interaction among students and self questioning is strongly encouraged and practicing comes first, before any theoretical knowledge. Through a series of concrete examples, the present paper describes the philosophy underlying the teaching in this course. We demonstrate that not only geometrical optics can be taught through experiments, but also that it can serve as a useful introduction to experimental physics. Feedback over the last 10 years shows that our approach succeeds in helping students to learn better and acquire motivation and autonomy. This approach can easily be applied to other fields of physics.